Konflik Antar Narapidana di Lembaga Pemasyarakatan Kelas I Cipinang dalam Perspektif Subkultur Penjara - Mubarokah, Adams Firdaus; Larasati, Nadia Utami (Deviance Jurnal Kriminologi, 2023)
This article explores the issue of conflicts that frequently arise among prisoners in correctional institutions. It seems that such conflicts have become common within the prison culture. The inmates have to live in overcrowded conditions, often beyond the capacity of the facilities, with inadequate provision of basic rights and being away from their families, which can worsen their situation. All of this can lead to increased stress levels, making it difficult to avoid conflicts. In this article, we will describe the types of conflicts that often occur in prisons and the factors that cause them. We carried out a qualitative approach using a structured interview method with two prisoners and two correctional officers. We used prison subculture theory to analyze existing problems. Our research results show that prison subculture is a phenomenon that forms in the prison environment because prisoners adopt the values and behavior patterns that occur in prison. This subculture influences prisoners in adapting to life in prison, which is harsh and limited. Conflict between inmates is a characteristic inherent in prison subculture. In prisons, there is competition, power, and differences in gangs and groups that often trigger serious conflicts between prisoners. This conflict can lead to physical violence, threats, and insecurity in prisons.